2021
DOI: 10.1111/jfpp.15284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an edible coating composed of whey protein concentrate and rosemary essential oil on the shelf life of fresh spinach

Abstract: Coating fresh vegetables is a useful strategy to maintain quality and prevent food waste. In this study, the effect of an edible coating composed of whey protein concentrate (WPC) and rosemary essential oil (REO) was evaluated on extending the shelf life of fresh spinach. The REO coating in 0.6% concentration decreased total microbial and coliform counts to 0.57, 0.23 log CFU/g, respectively, during storage. The coated sample with REO had the lowest decrease in the chlorophyll content on most days of the stora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The increase in the acidity of the samples can have multiple reasons, for example, it is related to the formation of dominant organic acids, oxalic acid, and malic acid. It can also be related to the activity of microorganisms and natural antimicrobial compounds in spices ( Abedi, Lakzadeh, & Amouheydari, 2021 ; Amirhossein Abedini, Sadighara, Sani, & McClements, 2023 ). The investigation of TVB-N during 14 days in the refrigerator and 96 h in the room showed that all the samples increased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…The increase in the acidity of the samples can have multiple reasons, for example, it is related to the formation of dominant organic acids, oxalic acid, and malic acid. It can also be related to the activity of microorganisms and natural antimicrobial compounds in spices ( Abedi, Lakzadeh, & Amouheydari, 2021 ; Amirhossein Abedini, Sadighara, Sani, & McClements, 2023 ). The investigation of TVB-N during 14 days in the refrigerator and 96 h in the room showed that all the samples increased significantly.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, whey has been successfully applied to develop milk protein-based active edible packaging systems as edible films/coatings in food products [68]. Abedi et al [69] developed an edible coating based on whey protein concentrate and rosemary essential oil to extend the shelf-life of fresh spinach. The developed material was able to decrease the total microbial and coliform growth.…”
Section: Animal-based Wastes (Meat and Dairy Products) For Packaging ...mentioning
confidence: 99%
“…Edible coatings have demonstrated their ability to protect foods [19,[24][25][26], but in recent years, the application of multilayered coatings have demonstrated the improvement of fresh fruit shelf life. In this technique, oppositely charged solutions are used to dip the fruit, creating a layer-by-layer coating that enhances fruit properties [27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%